The financial, health, and social crisis in Europe. Developments and cha-llenges from the Social Work perspective - Arredondo-Quijada, Rafael; Palma-García, María de las Olas; Ruiz-Mosquera, Ana Cristina (Universitat de Barcelona, 2023)
We conducted a descriptive documentary review study using a sequential design of the assessable indicators of Euro-pean social policies developed between 2008 and 2019. The period between the 2008 financial crisis and the current COVID-19 health crisis was studied using Eurostat indicators to compare variables related to social risk and the gover-nmental response offered by the sample countries to provide social protection. We attempted to understand the cu-rrent crisis by examining the key social factors and potential connections with previous trends in the development of social policies in the European Union. On this basis, we identified effective strategies for managing the crisis. The data suggest that, in general, the European social protection model has not prevented the growth of inequality and social risk, thus calling for new ways and approaches to the design, implementation, and assessment of public policies to ensure their effectiveness. These new strategies involve re-envisioning Social Work as a key profession and discipline to promote social transformation.
Keywords: Trabajo social; Politica social; Social work; Financial crisis; Health crisis; Social policies; Social indicators